1997
DOI: 10.1039/a606561i
|View full text |Cite
|
Sign up to set email alerts
|

Formation of racemic compound crystals by mixing of two enantiomeric crystals in the solid state. Liquid transport of molecules from crystal to crystal

Abstract: Mixing of powdered (؊)-and (؉)-enantiomer crystals in the solid state gives crystals of the racemic compound. This racemic crystal formation was followed by IR spectral measurement of a 1 : 1 mixture of (؊)-and (؉)-enantiomer crystals as a Nujol mull. As the formation of racemic crystals proceeds, the OH absorptions of the enantiomer disappear gradually and new OH absorptions due to the racemic compound appear. The formation of racemic crystals from enantiomer crystals has been studied for various kinds of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 30 publications
3
61
0
Order By: Relevance
“…This does not lead to single crystals but the melting point and the spectroscopic and photochromic properties are identical to those found for the crystallized material. It is not uncommon that bimolecular solid state reactions of this kind take place [9].…”
mentioning
confidence: 99%
“…This does not lead to single crystals but the melting point and the spectroscopic and photochromic properties are identical to those found for the crystallized material. It is not uncommon that bimolecular solid state reactions of this kind take place [9].…”
mentioning
confidence: 99%
“…However, it is most likely that there are hydrogen bonds between the OH groups of neighboring BN derivatives, as is found in the case of unsubstituted BN crystals. 2 On mixing/grinding with BQ crystals, BN derivatives changed their hydrogen bond partners from naphthol hydroxyl to carbonyl groups of BQ. In the adduct crystal I, (R)-6,6Ј-diBrBN molecules are hydrogen bonded to the neighboring (R)-6,6Ј-diBrBN molecules as well as the carbonyl oxygen atoms of BQ.…”
Section: Adduct Crystal Formationmentioning
confidence: 99%
“…However, recent reports have shown that, even inside crystals, molecules are not necessarily strictly constrained. [1][2][3] Previously, we reported formation of a red adduct crystal of the charge-transfer type (X-I) by grinding crystals of racemic bis-␤-naphthol (rac-BN) and benzoquinone (BQ) in an agate mortar. 4 Evidence for the formation of a new crystal was obtained by X-ray powder diffractometry, which revealed the induction of a new set of peaks with time and the concurrent disappearance of the original peaks.…”
mentioning
confidence: 99%
“…(2) and - [4,5]decane (3) and interpret the experimental results in the light of the crystallographic data for neat 2 and 3. 7 We chose the systems 1-2 and 1-3 for the first mechanistic AFh4 investigation of a solid-solid clathration. The data indicate that large-scale resolution of solid volatile racemates can be achieved conveniently even in the case of surface passivation.…”
Section: Introductionmentioning
confidence: 99%